Plants and animals diversity in Buqaty Mountain Area (BMA) in Hamadan Province, Iran - MAHDI REYAHI-KHORAM; MAJEED JAFARY; MOSTAFA BAYATI; REIHANEH REYAHI-KHORAM (Biodiversitas Journal of Biological Diversity, 2012)
Reyahi-Khoram M, Jafary M, Bayati M, Reyahi-Khoram R. 2012. Plants and animals diversity in Buqaty Mountain Area (BMA) in Hamadan Province, Iran. Biodiversitas 14: 190-194. Buqaty Mountain Area (BMA) is regarded as one of the genetic reserves of Hamadan province in Iran. BMA is highly important regarding variety of plant and animal species, but limited research work has been performed in this area in the field of biodiversity. Identifying the unique ecologic talents and capabilities and aesthetics of BMA is the most important objective of this study. This research was conducted during 2010 through 2011 in BMA to identify various plant and animal species through documentary and also direct field observations. With direct referring to the various regions of the studied area, plant samples were collected from different slope position and transported to field laboratory units. Sampling was made for every 20 meters increase in the height of area. Animal species of the area were identified too. Based on the results, about 44 valuable plantÂ species, 45 species of birds as well as 7 species of mammals have been identified in BMA. It is recommended that the area be declared an A prohibited hunting area by Department of Environment (DoE)Â of Iran for the conservation of flora and fauna in the study area.